Production of Si3N4 porous beads via carbothermal reduction and nitridation technique - Topates, Gulsum; Kalemtaş, Ayşe (Taylor & Francis Ltd, 2020)
Si(3)N(4)porous beads were produced from direct carbothermal reduction and nitridation of spheres composed of carbon+SiO(2)mixtures. A simple one-step sol-gel templating technique was used to prepare carbon+SiO2(molar ratio of carbon/SiO(2)was set as 4) containing spheres with a diameter of 2 mm. A natural and abundant biopolymer, alginate, is used as a sacrificial template to produce porous Si(3)N(4)ceramic beads. Carbothermal reduction and nitridation process was conducted at two different temperatures (1500 and 1550 degrees C) and atmospheres (pure nitrogen and 5% hydrogen in nitrogen) to observe the effect of process parameters on the yield of Si3N4. Porous beads with a smooth shape and without any deformation were successfully obtained after the carbothermal reduction and nitridation process. X-ray powder diffraction studies showed that the use of H(2)increased the amount of Si(3)N(4)formed by accelerating the reduction and nitridation reactions. Microstructural investigations revealed oxide addition changed grain morphology from fiber-like to short, angular geometry. This microstructural development showed that the addition of oxide powder increased the amount of liquid phase formed during the heat treatment process and changed carbothermal reduction and nitridation mechanism from vapor-solid to vapor-liquid solid.
Keywords: Sol-gel templating; carbothermal reduction-nitridation; porous Si3N4 beads